Analisis Penggunaan Media Pembelajaran Berbasis Teknologi dalam Pembelajaran IPAS Sekolah Dasar - Dian Puspita Sari; Yusdin Bin M Gagaramusu; Muhammad Aqil; Zulnuraini; Sri Wahyuni (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to analyze the use of technology-based instructional media in IPAS (Science, Social Sciences, and Environment) learning in Grade IV at SDN Inpres 2 Tanamodindi. The research employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results indicate that although the school is equipped with adequate technological facilities, their utilization remains low as teachers tend to rely on conventional teaching methods. The main obstacles identified are the lack of understanding and technical skills among teachers in operating technological media, as well as the challenges in adapting to curriculum changes. However, the implementation of technology-based media has been proven to enhance students’ interest and learning motivation, while also creating a more interactive classroom atmosphere. In conclusion, the appropriate use of technology-based instructional media can improve the quality of the IPAS teaching and learning process. Therefore, teacher training and mentoring, along with the development of innovative learning strategies, are essential to improve the quality of IPAS instruction.  Keywords: Elementary School, Instructional Media, IPAS, Learning Motivation, Technology